311 A Feasibility Study for a Multicenter Phase-III Randomized Clinical Trial of Encephaloduroarteriosynagiosis Revascularization for Symptomatic Intracranial Atherosclerosis. (April 2023) - Nisson, Peyton Lubbock; Quintero-Consuegra, Miguel D.; Chang, Daniel; Saver, Jeffrey L.; Chimowitz, Marc; Gonzalez, Nestor R.
Abstract : INTRODUCTION: Stroke due to intracranial-atherosclerotic-disease (ICAD) remains a major public health concern, accounting for more than one-tenth of all ischemic-strokes in the US. METHODS: New data from advanced cerebral imaging and angiographic studies showed that revascularization after indirect-bypass occurs earlier than appreciated before. A pilot study of EDAS in ICAD patients demonstrated angiographic neovascularization as early as 1 month. An NINDS-funded phase-II objective-performance-criterion trial demonstrated reduction in the rate of stroke and death from 21.1% in the medical group to 9.6% in the surgical group at 2 years, passing the threshold for advancement to phase III. In collaboration with the NIH-StrokeNet, a national feasibility survey was sent to sites across the country to evaluate the feasibility of a phase-III clinical trial of EDAS in ICAD. RESULTS: Among 72 surveys completed by prospective sites, 90% (n = 65) indicated interest in participating and 96% of these (n = 63) had neurosurgeons and anesthesiologists with sufficient experience in EDAS and cerebrovascular disorders. The mean number of direct/indirect cerebral bypass surgeries per year completed at the prospective 40 sites was 19 (Range = 10-37). StrokeNet sites cared for a median of 42.5 patients/site/year (IQR = 25-100 patients/site/year) who met enrollment criteria. With 40 participating sites, the rate of enrollment needed for successful recruitment of 516 patients in a phase-III trial is 0.28 patients/site/month (3-4 patients/year), which is an order of magnitude less than the number of relevant cases receiving care at the sites (3.54 patients/month). CONCLUSIONS: EDAS is a promising technique in the management of ICAD and its performance is feasible within 40 high volume institutions. Engagement of the neurosurgical community on revitalizing a surgical form of revascularization can expand the role of neurosurgery in stroke management.